Formulation Ratio Effectiveness of Green Metal Working Fluid (GMWF) as a Bio Alternative for Green Manufacturing - Balogun, Vincent Aizebeoje; Obasa, Victoria Dumebi; Ohikhuare, Ohiozoje Bobo; Akhimien, Jeremiah Odion; Ikalumhe, Wilfred Onoshiorena (ABUAD Journal of Engineering Research and Development (AJERD), 2024)
Metalworking fluid (MWF) is essential for ensuring quality products and extended tool life during machining operations. While there are various sources of MWF, the need to minimize health hazards associated with mineral-based metal working fluid now calls for more environmentally friendly green metal working fluid (GMWF) from bio-degradable sources. Also, the effectiveness of vegetable-based GMWF significantly depends on the degree of functionalization. Though some studies considered the issue, the comparative analysis of the effect formulations (variation in concentration) of the constituting elements of the GMWF, especially for the base vegetable oil under consideration; has been grossly underreported. In this study, a GMWF emulsion has been developed from soybeans, palm fruits, and coconut with varying formulation ratios. Physicochemical characterization such as flash point, fire point, pour point, pH, density, and viscosity of the developed GMWF were analyzed. Also, a performance evaluation of the said GMWF was carried out and the investigation has shown that the physicochemical properties of the developed GMWF matched, as a potential substitute for conventional mineral-based MWF. Additionally, a performance evaluation conducted during a mechanical machining operation revealed that the GMWF showed an improved surface roughness of about 10.77% compared to conventional mineral MWF. Observations during the machining operation further revealed that the formulated GMWF demonstrated some level of environmental tolerance as it was not associated with misting or the discharge of fumes. The research outcome will impact green machining science and MWF technology for sustainable mechanical machining and cutting fluid development.